Analysis of Elfan Bookless Library System Innovation at the Barru Regency Library and Archives Office - Nasaruddin H.; Khusnul Hatimah; Risma Niswaty; H., Herman; Arhas, Sitti Hardiyanti (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
This qualitative study explores the innovation of the Elfan Bookless Library System at the Barru Regency Library and Archives Office. Data were collected through observation, interviews, and documentation, with validity ensured via triangulation, negative case analysis, member checking, and extended observations. The findings reveal that the Elfan Bookless Library System enhances the reading experience by providing its own Wi-Fi network, allowing online book access. While the system effectively meets visitors’ needs, its Wi-Fi coverage is limited to 500 meters, posing a connectivity challenge beyond this range. Despite this, the system is accessible without special requirements; visitors only need a cellphone or Android device. User guidance is provided through tutorials on billboards and banners, and library staff offers additional support. This study highlights the Elfan Bookless Library System’s potential to innovate public library services, offering valuable insights into its advantages and limitations. These findings contribute to understanding how digital library systems can be optimized to improve user experience and accessibility in public libraries.